Manfaat Kombinasi Aromatherapy Massage Dengan Minyak Cengkeh Dan Terapi Latihan Terhadap Parameter Womac Pada Pasien Osteoarthritis Genu: Studi Kasus - Melviana Putri Rosari; Noraeni Arsyad; Zulfikar Hamid Wada (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Osteoarthritis (OA) of the knee is a degenerative joint disorder that often causes pain, stiffness, and limited function, thereby interfering with daily activities (Grässel & Muschter, 2020). Physical therapy interventions can be combined with complementary therapies such as aromatherapy massage using clove oil, which has analgesic and anti-inflammatory effects, as well as exercise therapy to improve function (Dewi Puspita et al., 2020, Tugba Kuru Colak et al., 2017). Describe the benefits of combining aromatherapy massage with clove oil and exercise therapy on WOMAC parameters in patients with knee OA. A descriptive case study of 3 patients with knee OA (based on radiological examination) who underwent a combination of clove oil aromatherapy massage and exercise therapy for 3 weeks (8 sessions). The primary outcome was WOMAC (pain, stiffness, physical function) measured before (T1) and after the intervention (T8) (Sahar Ahmed, 2016). The analysis was descriptive (comparison of pre- and post-scores). After the 8-session intervention, all three patients showed improvement (decrease) in total WOMAC scores and/or improvement in the pain, stiffness, and physical function subscales. These results indicate that the combination of clove oil aromatherapy massage and exercise therapy has the potential to help reduce complaints and improve functional ability in knee osteoarthritis (Dewi Puspita et al., 2020, Lanfeng Huang et al., 2017). The combination of clove oil aromatherapy massage and exercise therapy in this case study was beneficial for improving WOMAC scores in patients with knee osteoarthritis.